Chemistry of silica and zeolite-based materials : synthesis, characterization and applications - Douhal, Abderrazzak; Anpo, Masakazu, 1946- (Chemical, Physical and Biological Aspects of Confined Systems ;, 2019)
Chemistry of Silica and Zeolite-Based Materials covers a wide range of topics related to silica-based materials from design and synthesis to applications in different fields of science and technology. Since silica is transparent and inert to the light, it is a very attractive host material for constructing artificial photosynthesis systems. As an earth-abundant oxide, silica is an ideal and basic material for application of various oxides, and the science and technology of silica-based materials are fundamentally important for understanding other oxide-based materials. The book examines nanosolvation and confined molecules in silica hosts, catalysis and photocatalysis, photonics, photosensors, photovoltaics, energy, environmental sciences, drug delivery, and health. Written by a highly experienced and internationally renowned team from around the world, Chemistry of Silica and Zeolite-Based Materials is ideal for chemists, materials scientists, chemical engineers, physicists, biologists, biomedical sciences, environmental scientists, toxicologists, and pharma scientists. --- "The enormous versatility of silica for building a large variety of materials with unique properties has been very well illustrated in this book. The reader will be exposed to numerous potential applications of these materials - from photocatalytic, optical and electronic applications, to chemical reactivity in confined spaces and biological applications. This book is of clear interest not only to PhD students and postdocs, but also to researchers in this field seeking an understanding of the possible applications of meso and microporous silica-derived materials."--Professor Avelino Corma, Institute of Chemical Technology (ITQ-CSIC) and Polytechnical University of Valencia, Spain